Reinterpretasi Hukum Islam terhadap Pembagian Warisan Bagi Anak Pasca Kematian Orang Tua - Eka Cahya Putri; Della Puspita; Muhammad Fathan; Dwi Noviani. M.Pd. I (Student Scientific Creativity Journal, 2024)
In the modern era, social dynamics continue to develop, including in terms of inheritance distribution. The issue of dividing inheritance for children after the death of parents is increasingly complex, with various factors that need to be considered. This journal aims to answer and analyze the comparison of the inheritance process for GS as an only child upon the death of both parents according to the Islamic legal system that applies in Indonesia and ensure that Islamic law remains relevant and in accordance with the needs of children in modern times. This journal uses a qualitative approach with literature study methods and critical analysis. Data is collected from various sources, including scientific journals, news articles, and research reports. Research findings show that the distribution of inheritance to children after the death of parents is influenced by various factors, such as social norms, culture, religion and law. This journal refers to efforts to reinterpret Islamic law regarding the distribution of inheritance to children after the death of parents by considering the current social, cultural and political context. Current social dynamics, such as changes in family structure, individualism, and globalization, also influence the inheritance distribution process. The division of inheritance in this journal takes a deeper look at inheritance rights to GS. The condition of GS, who is still a child, is not legally competent to take legal action. In this case, GS's grandfather and grandmother from BA are the guardians based on the paternal lineage attached to them who are the guardians. Further research is needed to understand the complexity of inheritance division in different social contexts. It is necessary to provide education and outreach to the public about the importance of proper inheritance planning and in accordance with applicable social norms and Islamic law.